CAN THE DIRECT INSTRUCTION LEARNING MODEL ASSISTED BY DIGITAL VISUAL MEDIA IMPROVE THE SOCIAL SCIENCE LEARNING ACHIEVEMENT? - Utomo, Supri Wahyudi; Parji, Parji; Maruti, Endang Sri; Prayoga, Widya Galih; Nugroho, Muhammad Seto Adjie (JURNAL EDUSCIENCE, 2025)
Purpose –This study examines the effectiveness of the Direct Instruction (DI) learning model when supported by digital-visual media in improving the learning achievement of elementary school students in social studies. The study aims to determine whether integrating DI with digital-visual aids can significantly enhance students’ understanding and retention of social studies material.Methodology – This classroom action research is conducted through 4 stages: planning, implementation, observation, and reflection. The research subjects were 26 fifth-grade students and was conducted collaboratively with teachers at SDN Klegen 04.Findings – State the main results of the study. Numerical data may be included, but should be kept to a minimum. State the conclusions and implications. The DI learning model can improve students' social studies learning achievement. This is evidenced by students who get the same or higher scores than the KKM 70.00, increasing from cycle I to cycle II. In cycle I, the completion of learning outcomes reached a class average of 72.3. While in cycle II, the completion of learning outcomes on average increased by 84.8.Contribution – Who would benefit from this study? These findings suggest that combining Direct Instruction with digital-visual aids can effectively improve elementary students' academic achievement in social studies. Therefore, educators are encouraged to adopt this approach to foster more meaningful and impactful learning, particularly in content-heavy subjects like social studies.